THE EFFECTIVENESS OF THE RECOVERY METHOD FOR MALUKU U-16 SOCCER PLAYER MSA THORANA ARU - Ztella Rumawatine; Jems Sopacua (Journal of Sport Science and Fitness, 2023)
This study aims to determine the effectiveness of several recovery methods to reduce the fatigue level of soccer players. The sample of this study was Thorana Aru, Maluku U-16 soccer player, aged 16.26 Â± 2.5 years, with a body weight of 56.13 Â± 11.84 kg, consisting of 32 people. The sample was divided into four groups using random sampling, namely the control group, active recovery, massage, and combined recovery, with a total sample of 8 people for each group. The objects in this study were the fatigue index and lactic acid levels in the blood, which were carried out by the initial test before recovery and the final test after recovery. The results showed that analysis of the fatigue index in the active recovery, massage, and combined recovery sample groups (p<0.05) could reduce the fatigue index of soccer players. Testing lactic acid levels that occurred during active recovery and combined recovery (p<0.05) showed that the two sample groups were effective in reducing lactic acid levels, whereas testing lactic acid levels in the massage sample group (p>0.05) showed a decrease in lactic acid levels. Based on the results of the data analysis, it can be concluded that active recovery and combined recovery are effective in reducing the level of fatigue in soccer players.